1988
DOI: 10.1038/332462a0
|View full text |Cite
|
Sign up to set email alerts
|

The presence of malfolded proteins in the endoplasmic reticulum signals the induction of glucose-regulated proteins

Abstract: Two glucose-regulated proteins, GRP78 and GRP94, are major constituents of the endoplasmic reticulum (ER) of mammalian cells. These proteins are synthesized constitutively in detectable amounts under normal growth conditions; they can also be induced under a variety of conditions of stress including glucose starvation and treatment with drugs that inhibit cellular glycosylation, with calcium ionophores or with amino-acid analogues. Unlike the closely-related heat shock protein (HSP) family, the GRPs are not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
785
0
15

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,234 publications
(830 citation statements)
references
References 26 publications
18
785
0
15
Order By: Relevance
“…Western blotting showed that acidosis exposure increased levels of procaspase-12 as well as the active 46 and 35 kDa caspase-12 fragments, with peak expression levels at 6 to 12 hours after acidosis ( Figures 3A and 3C). Increased expression of the ER chaperone protein GRP-78 was also observed, consistent with an ER stress response (Kozutsumi et al, 1988). Astrocytes incubated with agents known to induce ER stress, tunicamycin, brefeldin A, and thapsigargin , showed a similar pattern of increased expression of procaspase-12 and the active caspase-12 fragments ( Figures 3B and 3D).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Western blotting showed that acidosis exposure increased levels of procaspase-12 as well as the active 46 and 35 kDa caspase-12 fragments, with peak expression levels at 6 to 12 hours after acidosis ( Figures 3A and 3C). Increased expression of the ER chaperone protein GRP-78 was also observed, consistent with an ER stress response (Kozutsumi et al, 1988). Astrocytes incubated with agents known to induce ER stress, tunicamycin, brefeldin A, and thapsigargin , showed a similar pattern of increased expression of procaspase-12 and the active caspase-12 fragments ( Figures 3B and 3D).…”
Section: Resultssupporting
confidence: 61%
“…Acidosis in this range also can reduce the activity of ER Ca 2 þ ATPase (Wolosker et al, 1997). Since protein misfolding and reduced ER Ca 2 þ are both known to cause ER stress (Kozutsumi et al, 1988;Paschen and Frandsen, 2001), acidosis could be an important factor contributing to the ER stress response after ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…ERp72 is an abundant, ubiquitous, stress-inducible protein with calcium-binding capacity [132,135,136,[162][163][164][165] that differs from other PDI-like proteins in having three active thioredoxin domains rather than two. The domain distribution is c-a o -a-b-bh-ah (see Figure 3).…”
Section: Erp72mentioning
confidence: 99%
“…6 The second response is upregulation of genes encoding ER chaperone proteins such as BiP/GRP78 and GRP94, enzymes including protein disulfide isomerase (PDI) and peptidyl-prolyl isomerase, and structural components of the ER including sarcoplasmic ER Ca 2 þ -ATPase 2 (SERCA2), to increase the protein-folding capacity in ER. [7][8][9] In addition to these genes, recent studies revealed that genes involved in translational recovery, amino-acid import, glutathione biosynthesis and protection against oxidative stress are also upregulated. 10 In a later phase, components of ER-associated degradation (ERAD), including ER degradation-enhancing a-mannosidase-like protein (EDEM), are transcriptionally induced to eliminate misfolded proteins in the ER by the ubiquitin-proteasome system.…”
mentioning
confidence: 99%